Transparency And Public Participation as Determinants of Financial Management Accountability - Sri Martina; Djuli Sjafei Purba (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to analyze the influence of transparency and public participation on financial management accountability at the urban village level in Siantar Sitalasari District, Pematang Siantar City. The research employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) with 100 community respondents selected through purposive sampling. The findings reveal that transparency has a positive and significant effect on financial management accountability. Conversely, public participation does not have a significant effect on accountability. The R-Square value of 0.917 indicates that transparency and public participation jointly explain 91.7% of the variance in financial management accountability. Additionally, the Q² value of 0.666 demonstrates very strong predictive relevance of the model. These results confirm that transparency is the primary determinant of accountability, whereas public participation has not yet contributed meaningfully. The study highlights the need to strengthen public information disclosure and enhance community budget literacy to support accountable financial governance at the urban village level